Healing of oblique tooth root fracture concomitante with coronal fragment extrusion in permanente dentition: A case report - Propheta,Lucimara Aparecida (2023)
Abstract This case report describes a favorable healing outcome of the immediate management of an oblique tooth root fracture in the middle third concomitant with coronal fragment extrusion in a permanent maxillary left central incisor of a healthy 14-year-old female patient. The clinical exam showed incisal irregularity, local bleeding, increased mobility, and axial displacement of the maxillary left central incisor. The coronal fragment was repositioned and stabilized with a flexible splint for four weeks. The parents and the patient received medication prescriptions and instructions. Clinical and radiographic conditions remained satisfactory at the 4-week, 6-month, and 12-month follow-ups. Thermal and percussion tests confirmed pulp vitality after 12 months. Hard tissue formation between segments was observed in the radiographic examination and cone-beam computed tomography. In conclusion, the immediate conservative therapeutic showed satisfactory clinical and radiographic results.